Vitamin B5 and vitamin U review: justification of combined use for the treatment of mucosa-associated gastrointestinal pathologies - Shichkin, Valentin P. (Frontiers in Pharmacology, 2025)
Inflammatory and erosive lesions of the gastrointestinal mucosa encompass many conditions presenting significant challenges to public health worldwide. Amidst the quest for effective treatments, the attention of researchers has turned towards the potential therapeutic impact of bioactive nutrients, notably vitamin B5 (pantothenic acid) and vitamin U (S-methylmethionine). This review delves into the current understanding of the impact of these vitamins on the gastrointestinal system, analyzing their mechanisms of action and giving clinical evidence of the effectiveness of the combined application of these vitamins in the management of erosive gastrointestinal diseases.